Clinical profile of febrile encephalopathy patients at a tertiary care hospital in India: A retrospective study - Sanjeev Sengupta; Ashish Kumar Shukla; Kunal Kishore; Jitesh Goel; Amlan Ghosh (Journal of Acute Disease, 2023)
Objective: To investigate demography, etiology, and clinical profile and to analyze the outcomes of patients presenting with febrile encephalopathy at a tertiary care center in Eastern India. Methods: This retrospective, observational study included a total of 50 patients (>18 years) who presented with fever and encephalopathy. All patients underwent blood analysis; culture test for blood, urine, sputum, cerebrospinal fluid, and other body fluids; chest and abdominal ultrasonography; neuroimaging; polymerase chain reaction test, and other relevant tests as and when applicable. Results: The mean age of all enrolled patients was (58.0±16.0) years with male to female ratio of 1.27:1. Viral encephalitis was diagnosed in 16 (32%) patients, sepsis-associated encephalitis in 14 (28%), bacterial meningoencephalitis in 8 (16%) and tuberculosis meningoencephalitis in 5 (10%). The mean hospital stay was 10 (4, 17) days. At 6-month follow-up, 10 (20%) patients died, 10 (20%)patients recovered with sequelae (cognitive impairment, critical careneuropathy, etc.), and 30 (60%) patients recovered without sequelae. A statistically significant association was noted between GlasgowComa Scale (<8) and mortality rate (P=0.02). Conclusions: Primary central nervous system infection is the mostfrequent etiology of febrile encephalopathy and viral encephalitisis the most common etiological cause. Accurate, systematic, timelydiagnosis and management are prime factors to reduce mortality andmorbidity.